The extraction of crude enzyme of lipase from Penicillium candidum PCA 1/TT031 by way of solid state fermentation - Alhelli, Amaal M.; Abd Manap, Mohd Yazid; Mohammed, Abdulkarim Sabo; Mirhosseini, Seyed Hamed; Sukor, Rashidah; Mohammed, Nameer Khairullah; Khalil, Eilaf Suliman; Meor Hussin, Anis Shobirin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Solid-state fermentation (SSF), which is an excellent alternative for industrial enzyme production, entails the exploitation of cheap agro-industrial residues (low priced culture media). This paper delves into the cultivation of mould (GRAS Penicillium candium PCA 1/TT031) using wheat bran (WB) as the culture media. The parameters for crude enzymatic extraction of lipase production were optimized to achieve the highest possible lipase activity. An incubation period of 7 days (3.06 U/g WB), 2% of tributyrin (5.43 U/g WB), meat peptone equal to 2% (5.2 U/g WB), moisture content of 50% (v:w) (6.6 U/g WB), initial pH of 9.0( 8.6 U/g WB), inoculum size of 5×106 spore/g of WB (11.3 U/g WB), an incubation temperature of 20°C (13.6 U/g WB), and an extractant consisting of phosphate buffer pH 7.0 (14.7 U/g WB) were the conditions applied for this study.